Ascorbate electro-oxidation by modified electrodes: Polypyrrole and polypyrrole/Ni(OH)(2) composite thin films - da Silva, Marcelo Rodrigues [UNESP]; Ferreira, Marcelo Silva; Dall'Antonia, Luiz Henrique (Elsevier B.V. Sa, 2012)
The present paper describes the utilization of polypyrrole and the composite of polypyrrole doped with nickel hydroxide modified electrodes toward the catalytic oxidation of ascorbate. Films were potentiostatically deposited onto a glassy carbon surface and Fluor-doped tin oxide glass for different times. The physical characterization was performed using the low angle X-ray diffraction technique. Furthermore, the films were electrochemically characterized using cyclic voltammetry. The X-ray diffraction results show the existence of different polymorphic phases of nickel hydroxide in the polymer matrix, and the beta-Ni(OH)(2) phase appears to be dominant. The cyclic voltammetry profile in KOH solution shows the presence of two redox peaks that are related to the Ni-II/Ni-III and Ni-III/Ni-II couples, at approximately 0.5 and 0.35 V, respectively. The reversible electro-oxidation of ascorbate was observed on the surface of the polypyrrole and composite films. The analytical curves obtained using voltammetric techniques show a linear relationship between the faradaic current and the increase of the ascorbic acid concentration. The sensitivity of these films, which is obtained from the slope of the analytical curves, shows that the composite film is more electroactive than the polypyrrole film: 133.4 mA L mol(-1) cm(-2) and 83.8 mA L mol(-1) cm(-2), respectively. The rate constants of the catalytic ascorbate electro-oxidation were also reported, where the mean values were found to be 217.74 M-1 s(-1) and 54.37 M-1 s(-1), for the composite and polypyrrole films, respectively. The low cost of polypyrrole doped with Ni(OH)(2) composite electrodes presents a more selective and high sensitivity to determine ascorbic acid concentration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Polypyrrole; Nickel hydroxide; Ascorbate; Electro-oxidation